NECESIDAD DE INCORPORAR EN LA LEY ORGÁNICA DE ELECCIONES, SANCIONES A LOS PARTICIPANTES EN LAS CAMPAÑAS ELECTORALES QUE AFECTEN LO MORAL, ÉTICO, Y HUMANO DE LOS CANDIDATOS Y DE LA SOCIEDAD EN EL ECUADOR - Sánchez González., Andrea Paola (2016)
Society, culture and the Ecuadorian political system are in a process of change multifaceted that draw a new praxis and ever new forms of political conflict resolution, derived from trends on a universal scale faced by the most diverse contexts and countries, marked by capitalist globalization; in this context, the turbulence and rapid changes, coexistence of postmodernism with modern smack, has changed the role and impact of the mass media in our societies, as agents of political and cultural socialization that attempt to homogenize the various cultures and defining the guidelines not only economic, but political, social and cultural countries. On the other hand, he attends a reconfiguration of the political parties, which are facing huge systemic crisis of representation and aggregation of claims and pluralistic interests, thus losing its ability to dialogue in society against the State, emerging civil society, which is called upon to deal with increasingly political public space, defining it on a daily basis and thereby pressuring the powers of the States well as to the various political actors, towards greater democratization of the Nations. In this context, a genuine dispute is being recorded for the public sphere, by political, economic and social actors to influence the definition of the public agenda, so that their interests will prevail and have possibilities for resolution; against this background, it is important to know if the contents of political messages, and on the other hand, the use of media space, are